Growth, Yield and Varietal Responses of Cassava to time of Planting into Plantain Stands in a Plantain/Cassava Intercrop in Akure, South-West Nigeria - Aiyelari, P.O; Odede, A.N; Agele, S.O (Journal of Agronomy Research, 2019)
A field experiment was carried out at the Teaching and Research Farms of The Federal University of Technology Akure to evaluate the responses of cassava varieties to time of planting in plantain-based intercropping system in the rainforest zone of Nigeria. The objectives were to identify the more compatible cassava variety for intercrop with plantain examine e the appropriate time to introduce cassava varieties into plantain/cassava intercrop and to identify the more compatible cassava variety for intercrop with plantain. The experiment involved the use of two varieties of cassava (TME 419 non branching and TMS 98/0581 moderately branched) planted at spacing of 1 x 1 m into the alleys of false horn plantain variety space at 3 x 2 m. The treatments were sole plantain, sole cassava varieties (TME 419 poorly branched variety and TMS 0581 branching variety), plantain + he respective cassava varieties (TME 419 and TMS 98/0581) at the same time, and plantain + the respective cassava varieties (TME 419 and TMS 98/0581) at 4 weeks after planting>the treatment plot size was 9 m x 6 m. The plantains and the two cassava varieties were planted sole as the control treatments. The introduction of cassava into plantain as intercrop was carried out at different times which were; at the same time with plantain, and at four (4) weeks after planting plantain. Data on growth parameters such as; plant height, pseudo-stem girth, number of leaves were taken for plantains, while plant height, stem girth, number of leaves, number of branches, height at branching were taken for cassava at 4, 8, 12, 16, 20 and 24 weeks after planting (WAP). Yield parameters such as; bunch weight, number of fingers, number of hands, length of fingers, girth of fingers, weight of hands, weight of fingers were taken for plantains while number of tubers, weight of tubers, girth of tubers, length of tubers, fresh root yield, shoot biomass, were taken for cassava at harvest. The data collected were subjected to statistical analysis. The results showed a higher growth and yield performance for TME419 (49.2 t/ha) and TMS98/0581 (45.7 t/ha) planted sole, and TME 419 (39.5 t/ha) intercropped at planting compared to TMS 98/0581 (24.4 t/ha) intercropped at planting, TME 419 (21.7 t/ha) and TMS 98/0581 (15.7 t/ha) intercropped at 4 week after planting (WAP), respectively. But there was no significant difference (P<0.05) recorded for the growth of plantain, whereas the yield of sole plantain was higher and differed significantly (P<0.05) from the yields of intercropped plantain. All the treatment combinations had land equivalent ratio (LER) and area time equivalent ratio (ATER) greater than 1. Plantain + TME 419 intercropped at the same time recording the highest LER and ATER (1.48 and 1.5) while plantain + TMS 98/0581 had the least 1.11 and 1.14 respectively. The cost benefit analysis for the treatment combinations showed that TME 419 planted sole had the highest return of ₦3.567 per ₦1 invested, TME 419 intercropped at the same time gave a return of ₦3.416 per ₦1 invested, which was greater than other intercropped treatments. Intercropping cassava with plantain at the same time, as well as the use of TME 419 variety gave the best performance in terms of growth, yield, land equivalent ratio, area time equivalent ratio and returns on investment. This combination are recommended for plantain-based intercropping system involving cassava in the study area.
Keywords: Intercropping; resource use; competition efficiency; food; security; plantain; cassava.